First and target language use in public language education for young learners: Longitudinal evidence from Mexican secondary-school classrooms. (October 2016) - Izquierdo, Jesús; García Martínez, Verónica; Garza Pulido, María Guadalupe; Aquino Zúñiga, Silvia Patricia
Abstract: Reforms in public education favour the introduction of English as a foreign language at a young age. These reforms aim to help young learners achieve a high level of communicative performance in English by the end of public education. In language classrooms, the meaning-oriented use of English in teacher discourse can potentially facilitate language production and comprehension among learners and thereby provide language acquisition opportunities. This quantitative, descriptive study examined the use of English and Spanish in teacher discourse in terms of amount and purpose in Mexican secondary-school classrooms, where learners were completing the last language learning cycle in the national curriculum. Over two months, 45 h of regular classroom instruction were video-recorded in nine schools across five geographical areas of Southeast Mexico for analysis. The results indicate that teacher L1 overreliance and a lack of communicative purpose for the use of the L2 constitute shared and systematic features of public language pedagogy for young learners in the observed classrooms. These results are congruent with those from other international contexts and raise concerns about the effectiveness of language teaching to help young learners become competent users of English through public education.